The (26)Al-(26)Mg systematics of FeO-rich chondrules from Acfer 094: two chondrule generations distinct in age and oxygen isotope ratios - Hertwig, Andreas T. (Geochim Cosmochim Acta, 2019)
The (26)Al-(26)Mg ages of FeO-rich (type II) chondrules from Acfer 094, one of the least thermally metamorphosed carbonaceous chondrites, were determined by SIMS analysis of plagioclase and olivine/pyroxene using a radio frequency (RF) plasma oxygen ion source. In combination with preexisting (26)Al-(26)Mg ages of FeO-poor (type I) chondrules, the maximum range of formation ages recorded in chondrules from a single meteorite is determined to help provide constraints on models of material transport in the proto-planetary disk. We also report new SIMS oxygen three-isotope analyses of type II chondrules in Acfer 094. All but one of the plagioclase analyses show resolvable excesses in (26)Mg and isochron regressions yield initial (26)Al/(27)Al ratios of type II chondrules that range from (3.62 ± 0.86) × 10(−6) to (9.3 ± 1.1) × 10(−6), which translates to formation ages between 2.71 (−0.22)/(+0.28) Ma and 1.75 (−0.11)/(+0.12) Ma after CAI. This overall range is indistinguishable from that determined for type I chondrules in Acfer 094. The initial (26)Al/(27)Al ratio of the oldest type II chondrule is resolved from that of all other type II chondrules in Acfer 094. Importantly, the oldest type I chondrule and the oldest type II chondrule in Acfer 094 possess within analytical error indistinguishable initial (26)Al/(27)Al ratios and Δ(17)O values of ~0‰. Ages and oxygen isotope ratios clearly set these two chondrules apart from all other chondrules in Acfer 094. It is therefore conceivable that the formation region of these two chondrules differs from that of other chondrules and in turn suggests that Acfer 094 contains two distinct chondrule generations.